Clonorchis sinensis Granulin Promotes Malignant Transformation of Hepatocyte Through EGFR-Mediated RAS/MAPK/ERK and PI3K/Akt Signaling Pathways - Wang, Caiqin; He, Qing; Yin, Yingxuan; Wu, Yinjuan; Li, Xuerong (Frontiers in Cellular and Infection Microbiology, 2021)
The biological functions of growth factor, such as granulins, have been explored in parasites, and we elucidated that Clonorchis sinensis granulin (CsGRN) promoted the metastasis of hepatocellular carcinoma in our previous study. However, it is still unclear for the malignant transformation role of CsGRN in normal human hepatocytes. In this study, by transfecting pEGFP-C1-CsGRN eukaryotic expression plasmid, a cell line with stable overexpression of CsGRN in normal hepatocyte (LO2-GRN cells) was constructed. The effects on cell proliferation were detected by carrying out cell counting kit-8 (CCK8) assay and colony formation assay. Additionally, we conducted flow cytometry analysis to determine whether the proliferation of CsGRN was due to cell cycle arrest. Subsequently, the migration ability and the invasion ability of LO2-GRN cells were evaluated through wound-healing assay and transwell assay. Meanwhile, the levels of the markers of RAS/MAPK/ERK and PI3K/Akt signaling pathways activation in LO2-GRN cells were assessed by quantitative RT-PCR and Western blot. Our results indicated that CsGRN promoted the proliferation of LO2 cells by regulating the expression of cell-cycle-related genes. Moreover, the overexpression of CsGRN regulates malignant metastasis of liver cells by inducing the upregulation of epithelial–mesenchymal transition (EMT) marker proteins. Furthermore, both mRNA and protein expression levels of p-EGFR, RAS, p-ERK, p-AKT, p-PI3K, and p-braf have been enhanced by CsGRN. These results showed that CsGRN promoted the malignant transformation of hepatocytes by regulating epidermal growth factor receptor (EGFR)-mediated RAS/MAPK/ERK and PI3K/Akt signaling pathways, which suggested that CsGRN could serve as a novel oncoprotein during Clonorchis sinensis–associated malignant transformation of hepatocytes.